The influence of three-dimensional effects on the performance of U-type oscillating water column wave energy harvesters. (October 2017) - Malara, G.; Gomes, R.P.F.; Arena, F.; Henriques, J.C.C.; Gato, L.M.C.; Falcão, A.F.O.
Abstract: This paper studies the dynamics and power extraction of a U-Oscillating Water Column (U-OWC) device. A three-dimensional hydrodynamic model, based on the boundary integral equations method, is implemented. The U-OWC width and wave direction are analysed and compared with a two-dimensional model based on the eigen-function expansion method. Results show that as the device width increases, the power extraction per unit width tends to the two-dimensional value. For small converter widths, which are expected to be implemented in practical applications, three-dimensional effects are relevant and provide a systematic improvement in power output per unit width, due to their influence in the device hydrodynamic characteristics. Highlights: We compare the response of a U-OWC wave energy harvester calculated by analytical and numerical techniques. Three-dimensional effects neglected by current analytical solutions are investigated. It is seen that the analytical solution underestimates the U-OWC response obtained by the numerical approach.